Memperkuat Motivasi Belajar dan Perencanaan Karier di Yayasan Tajaul Karomatu Desa Situ Gadung Kabupaten Tangerang - Widia Astuti; Lily Setyawati Kristianti; Subarto Subarto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Motivation and career planning are crucial factors in enhancing students’ academic achievement and preparing them for future career paths. To support both educators and students in these areas, a Community Service Program (PKM) was conducted at Yayasan Tajaul Karomatu, Desa Situ Gadung, Kabupaten Tangerang, on May 29, 2025. The program was implemented by three lecturers and five students from Universitas Pamulang and involved 23 participants, including teachers, educational staff, and students. The PKM activities were carried out through a structured process consisting of preparation, execution, and reporting stages. During the execution phase, participants engaged in material presentations, practical exercises, discussions, and question-and-answer sessions aimed at strengthening learning motivation and career planning skills. The results showed that participants demonstrated significant improvement in understanding the importance of motivation and strategic career planning. Teachers and staff reported an enhanced ability to motivate students and facilitate goal-setting, while students gained clearer insights into their academic and career aspirations. Overall, the PKM positively contributed to fostering a proactive educational environment, encouraging both educators and learners to engage in continuous self-improvement and career development planning. These outcomes underscore the effectiveness of targeted community service interventions in educational institutions.